Evaluation of direct sowing techniques and litter transposition for the emergence and establishment of Manduvi (Sterculia apetala (jacq). Karts.) In ecological restoration work in an area of degraded springs in the Pantanal Mato-grossense (Research, Society and Development, 2021)
The technique of forest restoration based on the direct sowing of native species, has shown to be promising when compared with the most used technique today, which is the planting of seedlings, mainly because it reduces expenses and labor. The objective of this study was to evaluate which direct sowing technique (in pits or haul) is more promising, and what is the influence of litter transposition after sowing, for emergence and initial establishment of the native species Sterculia apetala (Jaqc.) H. Karst. in ecological restoration in an area of degraded springs in the municipality of Cáceres-MT, Pantanal Mato-Grossense. In this experiment, two direct sowing techniques (in pits and haul) were analyzed in two different environments (with and without litter transposition), using the native plant S. apetala. All the sowing techniques analyzed were efficient, obtaining good percentages of emergence and establishment, however, direct sowing in pits with litter transposition (T2), proved to be the most efficient technique in all parameters evaluated for S. apetala in this experiment. The litter transposition after direct sowing (T2 and T4), showed a positive influence on the establishment of seedlings for all the parameters analyzed, causing more vigorous plants at the end of the experiment.